Killer Robots and Inauthenticity: A Heideggerian Response to the Ethical Challenge Posed by Lethal Autonomous Weapons Systems - Roden-Bow, Ashley (Conatus - Journal of Philosophy, 2023)
This paper addresses the ethical challenges raised by the use of lethal autonomous weapons systems. Using aspects of the philosophy of Martin Heidegger, the paper demonstrates that lethal autonomous weapons systems create ethical problems because of the lack of moral agency in an autonomous system, and the inauthentic nature of the deaths caused by such a system. The paper considers potential solutions for these issues before arguing that from a Heideggerian standpoint they cannot be overcome, and thus the development and use of lethal autonomous weapons systems should be resisted and prohibited.